ANALISIS KINERJA ORGANISASI DINAS PARIWISATA KABUPATEN SEMARANG (STUDI KASUS DI UPTD OBYEK WISATA CANDI GEDONGSONGO) - Istiyani, Istiyani; Yuniningsih, Tri (Journal of Public Policy and Management Review, 2019)
Tourism is a sector that has a large impact on the country incomes if it used optimally. Of course, an important factor to develop tourism sector is human resources. Competent human resources who are able to complete the tasks thoroughly are the determining factor for the success of the projects. In this case, performance of the organization needs attention. So, from time to time the programs are getting better. This study focus on performance of the organization that handle Gedong Songo Temple Tourism Object in Semarang District. Gedongsongo Temple is a historical heritage site that has a unique tourist attraction, a combination of natural and cultural appeal. The purposes of the study is to find out how performance of the organization, and also supporting and inhibiting factors at Tourism Department of Semarang District (Case Study of UPTD Gedongsongo Temple Tourism Object). In this study, performance of the organization was analyzed using dimensions of service quality, responsiveness, responsibility, accountability, effectiveness, and efficiency. The results of the study show that several dimensions have not been optimal, those dimensions are: service quality, responsiveness, and responsibility. While accountability, effectiveness and efficiency are optimal. Supporting factor on performance of the organization is technology, while the inhibiting factors are leadership and system. In order to optimize performance of the organization, it is necessary to fix the results of dimensions of the performance both quantity and quality, maximize the role of supporting factors and minimize inhibiting factors.